PENGAWASAN PARTISIPATIF MASYARAKAT PADA PILKADA SERENTAK TAHUN 2020 MELALUI PERANAN BAWASLU DITENGAH PANDEMI COVID19 - Imron Fadillah, (2021)
This paper examines the supervision of the General Election carried out by the Election Supervisory Body (Bawaslu) in the implementation of the Regional Head General Election through several participatory monitoring programs during the 2020 Covid-19 virus pandemic. The implementation of the 2020 Simultaneous Regional Head Election is different from the implementation of the general election. in normal conditions, considering that the 2020 Simultaneous Regional Head Elections were held during the Covid-19 pandemic. Public health concerns are a challenge for Bawaslu to maintain public participation in supervising the 2020 Simultaneous Regional Head Elections. Using descriptive qualitative methods through interviews and literature studies, this paper discusses the implementation of participatory supervision initiated by Bawaslu in the implementation of the Regional Head General Election. in the midst of the Covid-19 pandemic, as well as explaining what things contributed to the success and obstacles to the implementation of participatory supervision in the 2020 Simultaneous Regional Head Election in the midst of the Covid-19 pandemic.